PENGARUH KEMAMPUAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) GURU DAN BUDAYA KERJA TERHADAP KINERJA GURU (Di Sekolah Islam Ruhama Ciputat Tangerang Selatan) - Siskandar Siskandar; Akhmad Shunhaji; Andi Subandi (PMPP Lembaga Penelitian dan Studi Kebijakan, 2022)
This study aims to determine and examine empirical data on the influence of teachers' information and communication technology (ICT) abilities and work culture on teacher performance partially (alone) or simultaneously (together). The author uses a survey method with a regression approach to quantitative data obtained from the object of research. The research sample was taken from the entire population (saturated sample) totaling 65 teachers at the Ruhama Islamic School Ciputat, South Tangerang. Data was collected using a questionnaire/questionnaire, interviews, and documentation techniques. The type of analysis used is simple and multiple regression analysis which is described descriptively. The results showed that there was a positive and significant effect of teachers' ICT skills and work culture on teacher performance, either partially or simultaneously. Partially, the magnitude of the influence or coefficient of determination (R2) of teachers' ICT abilities and work culture on teacher performance are 30.5% and 61.1%, respectively. Meanwhile simultaneously, the magnitude of the influence or coefficient of determination (R2) of teachers' ICT abilities and work culture on teacher performance is 65.0%